(untitled) (Pain medicine, 2019)
This study is aimed to compare the difference of neutropenia with peripheral neuropathy condition, after administration of 3 hours and 24 hours Paclitaxel infusion in adjuvant therapy with PaclitaxelCarboplatin toward patient with ovarian carcinoma. The method that used was experimental research with samples randomized after consecutively recruited based on inclusive criteria. Before and every after chemotherapy, NCS was performed and differential count laboratories’ test and then analysed with Ttest and Chisquare test. The result showed that from three times administration of 3 hours PaclitaxelCarboplatin infusion group, the neutropenia condition after first up to third chemotherapy was 20 %, 30 %, 30 %, and the peripheral neuropathy condition was 30 %, 60 %, 50 % respectively. Meanwhile, in 24 hours PaclitaxelCarboplatin infusion group, the incident of neutropenia after first up to third chemotherapy was 40 %, 50 %, 40 %, and the incident of peripheral neuropathy was 20 %, 20 %, 20 % respectively. The statistic result was p > 0.05. Hence, there was no significant difference in neutropenia and peripheral neuropathy incident on two study group.